Effects of acute exercise on memory: Considerations of exercise intensity, post-exercise recovery period and aerobic endurance - Loprinzi, Paul D.; Roig, Marc; Tomporowski, Phillip D.; Javadi, Amir-Homayoun; Kelemen, William L. (Memory & cognition, 2023)
Accumulating research demonstrates that acute exercise can enhance long-term episodic memory. However, it is unclear if there is an intensity-specific effect of acute exercise on long-term episodic memory function and whether this is influenced by the post-exercise recovery period, which was the primary objective of this experiment. Another uncertainty in the literature is whether aerobic endurance influences the interaction between exercise intensity and post-exercise recovery period on long-term episodic memory function, which was a secondary objective of this study. With exercise intensity and post-exercise recovery period occurring as within-subject factors, and fitness as a between-subject factor, 59 participants (M age = 20 years) completed 12 primary laboratory visits. These visits included a 20-min bout of exercise (Control, Moderate, and Vigorous), followed by a recovery period (1, 5, 10, and 15 min) and then a word-list episodic memory task, involving an encoding phase and two long-term recall assessments (20-min and 24-h delayed recall). The primary finding from this experiment was that moderate and vigorous-intensity exercise improved memory function when compared to a non-exercise control. A secondary finding was that individuals with higher levels of aerobic endurance, compared to their lesser fit counterparts, had greater memory performance after exercise (moderate or vigorous) when compared to after a control condition. Additionally, individuals with higher levels of aerobic endurance, compared to their lesser fit counterparts, generally performed better on the memory task with longer post-exercise recovery periods. Future research should carefully consider these parameters when evaluating the effects of acute exercise on long-term episodic memory.